Apparent mineralocorticoid excess syndrome with nephrocalcinosis and renal complications: A case series of two siblings (Indian Journal of Case Reports, 2025)
Apparent mineralocorticoid excess (AME) syndrome is a rare autosomal recessive cause of secondary hypertension, especially in children and young adults. Its heterogeneous presentation often delays diagnosis. We report a case series of two siblings, born of a 2nd-degree consanguineous marriage, both with AME syndrome complicated by nephrocalcinosis. The elder sibling developed renal osteodystrophy, progressive renal dysfunction, and cardiovascular complications, whereas the younger sibling remained stable with early diagnosis and therapy. This case series highlights the prognostic impact of early diagnosis and treatment, as well as diagnostic challenges in differentiating AME from Liddle syndrome. Awareness is crucial in consanguineous populations where genetic risk is higher.